MENELISIK PROBLEMATIKA KURSUS BAHASA ASING DI ERA PANDEMI COVID-19: PROGRAM PENGAYAAN KEPADA PEMILIK KURSUS BAHASA ASING INTENSIF - Silalahi, Ronald Maraden Parlindungan; Christian, Michael; Fensi, Fabianus; Rembulan, Glisina Dwinoor (Universitas Bunda Mulia, 2022)
Technological developments and globalization require foreign language skills. This phenomenon causes the high urgency of linguistic competence. This existence has also sporadically triggered the emergence of various foreign language courses in Indonesia. However, this phenomenon seems to be shifting along with the outbreak of the Covid-19 virus. The pandemic era forced foreign language institutions to survive financially to cover operational costs as a result of significant changes before and after the pandemic. However, financial problems are not the only problems foreign language course institutions face—changes from conventional learning models oriented from face-to-face learning to online-based learning. Creating a language course institution changes the various dimensions in it. Research on various problems of foreign language courses in the pandemic era was conducted qualitatively through interviews and Focus Group Discussions (FGD) involving entrepreneurs of intensive foreign language courses in the Tangerang area and its surroundings. Through FGD, it was found that it was necessary to make massive and simultaneous adjustments by course institutions in this pandemic era. The adjustments referred to include changes in teaching methods and techniques and adjustments in terms of promotion. The findings in the FGD will be further developed through an enrichment program involving various parties, including students, teachers, and business owners, for intensive foreign language courses. Community Service Activities (PKM) are expected to have implications for competitiveness data and the ability of foreign language course institutions to survive during the pandemic but still maintain quality.